2x^2+10x+11=0
Put the constant on one side of the equation, and the x and x^2 terms on the other:
2x^2 + 10x = -11
Divide both sides by the coefficient of x^2, which is 2:
x^2 + 5x = -11/2
Take half the coefficient of x, square it, and add it to both sides:
x^2 + 5x + 25/4 = -11/2 + 25/4
x^2 + 5x + 25/4 = 3/4
Factor the left side.
(x + 5/2)^2 = 3/4
Notice the number inside the parantheses that you add to x is half the coefficient of x that we got in an earlier step--this will always be the case.
Take the square root of both sides, be sure to include the ± sign for the right side:
√[(x + 5/2)^2] = √(3/4)
x + 5/2 = ± √(3)/2
x = -5/2 + √(3)/2
and
x = -5/2 - √(3)/2
2007-06-28 13:04:37
·
answer #1
·
answered by slay_09 2
·
0⤊
0⤋
Divide everything by 2
x^2+5x+11/2=0
Subtract the 11/2 to the other side
x^2+5x+ ( )= 11/2+ ( )
x^2+5x+ (5/2)=11/2+(5/2)
(x+5/2)^2=11/2+5/2
(x+5/2)=Square root of 3i
2007-06-28 19:36:14
·
answer #2
·
answered by Nea 3
·
0⤊
0⤋
x² + 5x = - 11 / 2
x² + 5x + 25/4 = - 11/2 + 25/4
(x + 5/2)² = - 22/4 + 25/4
(x + 5/2)² = 3/4
(x + 5/2) = ± (1/2).â3
x = - 5/2 ± (1/2)â3
x = (-1/2).(5 ± â3)
2007-07-02 14:25:21
·
answer #3
·
answered by Como 7
·
0⤊
0⤋
2x²+10x+11=0
delta = 10² - 4*2*11
delta = 100 - 88
delta = 12
x = (-10 +/- \/12) : 2*2
x = (-10 + 2\/3) : 4 = -5 + \/3/2
x" = (-10 -2\/3) : 4 = -5 -\/3/2
Solution: {-5 + \/3/2 or -5 -\/3/2}
:>:
2007-06-28 19:34:38
·
answer #4
·
answered by aeiou 7
·
0⤊
0⤋
2x^2+10x+11=0
2(x^2 + 5x + 5.5) = 0
2[(x+2.5)^2 - (2.5)^2 + 5.5] = 0
2[(x+2.5)^2 - 6.25 + 5.5] = 0
2(x+2.5)^2 - 12.5 + 11 = 0
2(x+2.5)^2 - 1.5 = 0
2007-06-28 20:13:57
·
answer #5
·
answered by Kemmy 6
·
0⤊
0⤋
Purplemath, very good site
2007-06-28 19:29:19
·
answer #6
·
answered by JaxJagsFan 7
·
1⤊
0⤋